2006
DOI: 10.1093/molehr/gal068
|View full text |Cite
|
Sign up to set email alerts
|

PGE2 up-regulates EGF-like growth factor biosynthesis in human granulosa cells: new insights into the coordination between PGE2 and LH in ovulation

Abstract: LH and prostaglandin E(2) (PGE(2)) share many similar effects on the pre-ovulatory follicle. They can induce independently cumulus expansion, the resumption of meiosis and progesterone production. However, cyclooxygenase-2 (COX-2) inhibitors were found to hinder most of the LH-induced effects. Recently, EGF-like growth factors amphiregulin (Ar) and epiregulin (Ep) were found to be produced in response to LH stimulation and to induce cumulus expansion and oocyte maturation. We aimed at evaluating whether PGE(2)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
48
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 72 publications
(51 citation statements)
references
References 29 publications
3
48
0
Order By: Relevance
“…2), and UTMP (Supplementary Tables 1 and 2) were the major redundant candidates in our gene networks. While TNFAIP6, INHBA, EREG, and TNF were reported previously as potential candidates induced by LH in CCs in association with competence (Ben-Ami et al 2006, Feuerstein et al 2007, we reported herein an interesting gene network (Fig. 4) where the TNF seems to play a crucial and central role in CCs expansion and steroidogenesis via its interactions with several known genes as PTX3, TNFAIP6, gap junction protein a 1 (GJA1), and progesterone.…”
Section: Cell Signalingmentioning
confidence: 50%
“…2), and UTMP (Supplementary Tables 1 and 2) were the major redundant candidates in our gene networks. While TNFAIP6, INHBA, EREG, and TNF were reported previously as potential candidates induced by LH in CCs in association with competence (Ben-Ami et al 2006, Feuerstein et al 2007, we reported herein an interesting gene network (Fig. 4) where the TNF seems to play a crucial and central role in CCs expansion and steroidogenesis via its interactions with several known genes as PTX3, TNFAIP6, gap junction protein a 1 (GJA1), and progesterone.…”
Section: Cell Signalingmentioning
confidence: 50%
“…Moreover, the data of the present study indicate that BTC is not increased following FSH stimulation. Expression of BTC was found only in rodent ovarian follicles and was not reported in studies dealing with the EGF-like peptide expression in the pig (Yamashita et al 2007, Kawashima et al 2008, horse (Lindbloom et al 2008), macaque (Fru et al 2007), and human (Freimann et al 2004, Ben-Ami et al 2006. Taken together, it is obvious that the gonadotropin-induced expression of EGF-like peptides in mural granulosa and consequently in cumulus cells is a common mechanism of intrafollicular signaling in preovulatory follicles.…”
Section: Discussionmentioning
confidence: 86%
“…Recently, our group demonstrated that AngII stimulates the expression of PTGS2 mRNA in cultured bovine granulosa cells, which was potentiated by LH (Portela et al 2008). The involvement of the PTGS2 pathway in oocyte nuclear maturation has been previously demonstrated in sheep (Murdoch 1988(Murdoch , 1996, cattle (Nuttinck et al 2002, Calder et al 2005, mice (Takahashi et al 2006), humans (Ben-Ami et al 2006), and horses (Dell'Aquila et al 2004). In sheep, the systemic administration of indomethacin (nonselective PTGS inhibitor) resulted in suppression of the cumulus cell expansion and oocyte nuclear maturation, which were reversed by PGE 2 intrafollicular injection (Murdoch 1988(Murdoch , 1996.…”
Section: Introductionmentioning
confidence: 84%